The Video Online Learning Guides for Beginner College Students - Gunawan Wiradharma; Melisa Arisanty; Alpin Herman Saputra; Khaerul Anam; Anton Robiansyah (Universitas Lancang Kuning, 2020)
College students who do online learning will certainly feel different from conventional learning experiences, especially at the beginning level college students. They have discussions every week and work on assignments. Current learning is risky with plagiarism. In addition, there are still college students who do not know how to take part in online learning properly. Based on simple observations, they do not pay attention to the rules of working on discussions or assignments so well that a guide is needed in conducting online learning through community service activities. Our community service program in the field of education is to create video Online Learning Guides. This video consists of a Brief Overview of Online Learning, Work on Assignments, Search for Reference Lecture Assignments, Writing Quotations and Bibliography, and Collecting Assignments. After this video has been completed, we will request comments from college students in the 2020 period based on good video media criteria. The selection of respondent samples will be conducted at UPBJJ Universitas Terbuka Jakarta, Palembang and Mataram. The results of this community service activity are an online learning guide that can guide them in conducting online learning when conducting discussions, doing assignments, through collecting discussions and assignments. This video can be used anytime according to college student needs through easily accessible media and and can help college students get better grades.